2019
DOI: 10.1016/j.eurox.2019.100047
|View full text |Cite
|
Sign up to set email alerts
|

Are intra follicular estradiol and oocytes quality in women undergoing assisted reproductive technology different between the right and left ovaries? An observational study

Abstract: Objective Controlled Ovarian Stimulation (COS) for In-Vitro Fertilization (IVF) or Intracytoplasmic Sperm Injection (ICSI) is considered as an assisted reproduction technology. There are established structural and biological differences between both ovaries which may affect their responsiveness to COS. Whether the right or the left ovary responds superior to COS is a question which is unresolved in the literature. Study design The present study was conducted as a prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
2
2
Order By: Relevance
“…This observations differed significantly from reports in non-pregnant goats that established that the right ovaries were more active with higher weights and diameters than the left ovaries (2,19,20). Moreover, caprine ovaries with corpus luteum of pregnancy had higher weight compared with ovaries of similar age and reproductive stage that are devoid of corpus luteum of pregnancy (2,19). The differences observed in the left ovaries of pregnant Red Maradi goats could be attributed to increasing number of ovulations and developing copora lutea in twin pregnant goats when compared with single pregnant goats.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This observations differed significantly from reports in non-pregnant goats that established that the right ovaries were more active with higher weights and diameters than the left ovaries (2,19,20). Moreover, caprine ovaries with corpus luteum of pregnancy had higher weight compared with ovaries of similar age and reproductive stage that are devoid of corpus luteum of pregnancy (2,19). The differences observed in the left ovaries of pregnant Red Maradi goats could be attributed to increasing number of ovulations and developing copora lutea in twin pregnant goats when compared with single pregnant goats.…”
Section: Resultscontrasting
confidence: 99%
“…This result indicates that during pregnancy, the left ovaries were more active than the right ovaries in both single and twin bearing pregnancies. This observations differed significantly from reports in non-pregnant goats that established that the right ovaries were more active with higher weights and diameters than the left ovaries (2,19,20). Moreover, caprine ovaries with corpus luteum of pregnancy had higher weight compared with ovaries of similar age and reproductive stage that are devoid of corpus luteum of pregnancy (2,19).…”
Section: Resultscontrasting
confidence: 95%
“…The median AST was 28.5 IU/L, while the average ALT was 13.1 IU/L. [40,41] The mean value of AST in the follicular fluid per patient was 17.46 ± 9.59 IU/L in our study. The results of our study showed that there was no statistically significant difference between the 2 groups of patients that were first divided according to age (≤35 years and > 35 years) and then according to the outcome of the IVF process (negative and positive).…”
Section: Discussionmentioning
confidence: 41%
“…It remains unclear whether there are any ramifications in terms of ART outcomes. Among the scarce data comparing women with one and two ovaries, some studies have reported that the pregnancy rate is similar between the two groups, while others have found it to be less in single ovary women [ 8 - 9 ]. Similarly, others reported lower LBRs among women who underwent a unilateral oophorectomy (18.6%) compared with women who have two functional ovaries (25.4%) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%